Climate change and its effect on the vulnerability to zoonotic cutaneous leishmaniasis in Iran. Issue 3 (5th May 2021) - Charrahy, Zabihollah; Yaghoobi‐Ershadi, Mohammad Reza; Shirzadi, Mohammad Reza; Akhavan, Amir Ahmad; Rassi, Yavar; Hosseini, Seyedeh Zohreh; Webb, Nathaniel J.; Haque, Ubydul; Bozorg Omid, Faramarz; Hanafi‐Bojd, Ahmad Ali
Abstract: Zoonotic cutaneous leishmaniasis (ZCL) is an important vector‐borne disease with an incidence of 15.8 cases per 100, 000 people in Iran in 2019. Despite all efforts to control the disease, ZCL has expanded into new areas during the last decades. The aim of this study was to predict the best ecological niches for both vectors and reservoirs of ZCL under climate change scenarios in Iran. Several online scientific databases were searched. In this study, various scientific sources (Google Scholar, PubMed, SID, Ovid Medline, Web of Science, Irandoc, Magiran) were searched. The inclusion criteria for this study included all records with spatial information about vectors and reservoirs of ZCL which were published between 1980 and 2019. The bioclimatic data were downloaded from online databases. MaxEnt model was used to predict the ecological niches for each species under two climate change scenarios in two periods: the 2030s and 2050s. The results obtained from the model were analysed in ArcMap to find the vulnerability of different provinces for the establishment of ZCL foci. The area under the curve (AUC) for all models was >0.8, which suggests the models are able to make an accurate prediction. The distribution of all studied species in different climatic conditions showed changes. The variables affecting each of the studied species are introduced in the article. The predicted maps show that by 2050 there will be more suitable areas for the co‐occurrence of vector and reservoir(s) of ZCL in Iran compared to the current climate condition and RCP2.6 scenario. An area in the northwest of Iran is predicted to have suitable environmental conditions for both vectors and reservoirs of ZCL, although the disease has not yet been reported in this area. These areas should be considered for field studies to confirm these results and to prevent the establishment of new ZCL foci in Iran.